Current Trends and Challenges of the Development of Small and Medium-Sized Enterprises in the RA - Arakelyan, Marine («Տնտեսագետ» հրատ․)
In the contemporary world, more than ever, the sphere of small and medium entrepreneurship is considered to be the milestone which has a significant impact on the enhancement of the RA competitiveness, provision of stable economic growth and long-term economic development. This research has attempted to comprehensively analyze recent dynamics of the sector, hence representing the impact thereof on a range of socio-economic problems. The obstacles of the development of small and medium entrepreneurship have been discovered as a result of comprehensive analysis of economic indicators, as well as further possibilities of elimination and improvement of the existing flaws are being discussed in the present work. The target indicators in line with the level of realistic nature thereof defined by the RA Government programs and the strategy enforced by SMEs have been estimated by the author, in addition, the existing results of already implemented actions are analyzed highlighting the urgency of developing and introducing a distinguished system of tax privileges as a long-term development precondition of the spheres.
Keywords: Management